Alteration in mandible form and size in patients with impacted third molar (Research, Society and Development, 2021)
The third molars when misaligned, can cause complications for the patient, and in practice, especially in oral surgery and orthodontic field.This study aims to analyze changes in the shape and size of the jaw bone structure associated with the impact of third molars from geometric morphometry.This is a cross-sectional study, carried out with 110 panoramic radiographs of patients aged 18 to 25 years, attended at the Dentistry Module of the State University of Southwest Bahia. After obtaining panoramic radiographic images, measurements were made, followed by the generalized analysis of Procrustes, Discriminant function, cross-validation and Mahalanobis distance. There was no significant difference in the size of the mandible between the genders of the groups with and without impacted third molars (p> 0.05). For the shape of the mandible, significant differences (p